Systematic review on the attributes of resident satisfaction measurement in the facility management context - Ramli, A. M. A.; Harun, A. Nahar; Mohd Nawi, M. N.; Haron, N. A. (Penerbit Akademia, 2021)
Resident satisfaction with the building maintenance services rendered by the property management company is vital to the quality of people's life in the residential buildings. Resident satisfaction measurement generally depends on the service quality of the building maintenance services offered by the property management company. However, there were too many attributes that have influenced resident satisfaction, as highlighted in previous research. In fact, some of them were duplicated and redundant. Thus, the aim of this paper is to identify and simplify the attributes that contribute to resident satisfaction in the building maintenance services. For this purpose, the researchers carried out a systematic review of the most recent articles from 2009 to 2019. Researchers also have considered a few articles before 2009 with the opinion that articles were useful to support the present study. Researchers conducted content analysis by systematically analysing and reviewing previous research publications on service quality dimensions used for users' satisfaction measurement in the facility management context. Past researches have reported on 45 service quality dimensions that have been considered for users' satisfaction evaluation in the facility management field. The findings showed that the identified attributes suggested in the previous works in the facility management field were for a specific and different types of building. In this paper, the researchers suggest a comprehensive range of 18 service quality dimensions including cleanliness, general maintenance and assurance service quality dimension that are useful for measuring resident satisfaction with building maintenance services of the high-rise residential buildings. This finding will benefit the property management companies with valuable information on the attributes that they could rely on to measure resident satisfaction towards building maintenance services. In fact, it provides a clear understanding of service quality dimensions and facilitates future researchers on the appropriate attributes to be considered in evaluating resident satisfaction with the high-rise residential building maintenance services in their future research.